2023
DOI: 10.21203/rs.3.rs-2531419/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-Throughput Reprogramming of an NRPS Condensation Domain

Abstract: Engineered biosynthetic assembly lines could revolutionize the sustainable production of bioactive natural product analogues. While yeast display is a proven, powerful tool for altering the substrate specificity of gatekeeper adenylation domains in nonribosomal peptide synthetases (NRPSs), comparable strategies for other components of these megaenzymes have not been described. Here we report a high-throughput approach for engineering condensation (C) domains responsible for peptide elongation. We show that a 1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 71 publications
0
5
0
1
Order By: Relevance
“…For example, condensation reactions can also be assayed in high throughput. We recently showed that a displayed C–A–T domain equipped with a short docking domain could productively interact with an upstream module in solution to produce amide products tethered to the yeast surface, an activity we exploited to alter the substrate specificity of the displayed C domain . Extension to other bio-orthogonal labeling methods to enable variation of substrate side chain preferences or harnessing the power of iterative directive evolution , would further expand the range of problems that can be tackled with this assay platform.…”
Section: Discussionmentioning
confidence: 99%
“…For example, condensation reactions can also be assayed in high throughput. We recently showed that a displayed C–A–T domain equipped with a short docking domain could productively interact with an upstream module in solution to produce amide products tethered to the yeast surface, an activity we exploited to alter the substrate specificity of the displayed C domain . Extension to other bio-orthogonal labeling methods to enable variation of substrate side chain preferences or harnessing the power of iterative directive evolution , would further expand the range of problems that can be tackled with this assay platform.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all mutants maintained similar or even higher turnover rates (k cat ) for Piz between 2.8 and 5.0 min À 1 that are all well in the range of typical peptide formation rates of NRPSs. [51,52] However, the Michaelis-constant (K M ) dramatically increased for Pro from 0.14 mM (GrsB1) to 10 mM (GrsB1-AYA) after the first round of directed evolution, and then became undetectable in subsequent rounds. In contrast, the K M for Piz dropped from 9.2 mM in GrsB1 to 2.4 mM in GrsB1-MWG.…”
Section: Methodsmentioning
confidence: 99%
“…32,33 In a separate study, the corresponding residues were modified in the surfactin NRPS enzyme SrfAC to incorporate non-native fatty acid substrates. 34 However, the mechanisms underlying the substrate specificity of typical Cdomains from elongation modules with amino acyl or peptidyl substrates remain unknown. Additionally, how D C L and L C L domains distinguish between L-or D-configured donor substrates remains elusive.…”
Section: ■ Introductionmentioning
confidence: 99%